2018
DOI: 10.1177/0743558418755686
|View full text |Cite
|
Sign up to set email alerts
|

“Who Knows Me the Best and Can Encourage Me the Most?”: Matching and Early Relationship Development in Youth-Initiated Mentoring Relationships with System-Involved Youth

Abstract: Youth-initiated mentoring (YIM), in which youth select adults from within their communities to serve as mentors in relationships that are formalized through mentoring programs, has the potential to redress problems faced by many mentoring programs that could adversely affect system-involved youth, such as volunteer attrition and premature match closures. However, only a few programs have implemented YIM, and there is little research on this approach. This qualitative interview study examines the formation of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…In addition to previous qualitative research on the YIM approach (Schwartz et al, 2013; Spencer et al, 2016, 2018), our findings highlight the importance of the positioning process to become a YIM. The findings suggest what professionals call the natural paradox : How can professionals intervene to optimize relationship quality of the natural mentoring relationship without professionalizing this relationship too much?…”
Section: Conclusion and Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition to previous qualitative research on the YIM approach (Schwartz et al, 2013; Spencer et al, 2016, 2018), our findings highlight the importance of the positioning process to become a YIM. The findings suggest what professionals call the natural paradox : How can professionals intervene to optimize relationship quality of the natural mentoring relationship without professionalizing this relationship too much?…”
Section: Conclusion and Discussionsupporting
confidence: 67%
“…The latter underscores the notion that parents are important during the mentor selection process. Previous research has shown that collaborating with parents during the selection process is appreciated and empowers them to suggest mentors or vetoing mentors they felt were not a good fit (Spencer, Gowdy, Drew, & Rhodes, 2018). Future research should indicate whether a natural mentor with “footing” increases epistemic trust in parents and youth (Harre et al, 2009), enabling the adolescent to benefit from the knowledge available in the social network (Bronfenbrenner & Morris, 2007; Fonagy et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recalls the tendency towards negative perceptions around helpseeking (Pryce, Napolitano, & Samuels, 2017; Seita, Day, Carrellas, & Pugh, 2016) associated with subgroups of young people aging out of care. Such limitations can potentially be addressed through a range of approaches that focus on building socio-relational skills and strengthening relationships with specific non-parental adults (e.g., Greeson & Thompson, 2017; Hall & Jones, 2018; Nesmith & Christophersen, 2014; Spencer, Gowdy, Drew, & Rhodes, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of mentoring experiences that promote the relationship include demonstrating consistency and being fully present (Smith et al, 2015), and having knowledge of the youth's past along with demonstrating acceptance (Spencer, Gowdy, Drew, & Rhodes, 2018). The facilitation of an effective mentoring connection also requires flexibility, good listening skills, empathy, and trustworthiness (Lakind, Eddy, & Zell, 2014).…”
Section: Introductionmentioning
confidence: 99%